A Thousand Bim: A Rapid Value-Simulation Approach to Developing a BIM Tool for Supporting Collaboration during Schematic Design. (March 2014) - Park, Ju Hong; Nagakura, Takehiko
The purpose of this study is to develop a BIM-based plug-in that is able to assist a collaboration among heterogeneous professionals. The tool will enable them to communicate in the same language, articulate criteria and priorities in multiple perspectives, and to share rapidly simulated evaluations of schematic design variations. Among many barriers that block collaborations among professionals, a quintessential barrier in the building and design industries may be epistemological rather than physical. The professionally different ways of thinking, expertise, values, and priorities can be a block on the collaborative development process of architectural design projects. This paper takes the example of the relationship between developers and architects, who tend to have different evaluation criteria. A real-time value simulation tool is introduced as a means to generate possible building typologies on a given project site, with computation of expected total values expressed in simple financial terms.